2018
DOI: 10.1155/2018/1367801
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Implications of Platinum Nanoparticle Exposure: Stimulation of Intracellular Stress, Inflammatory Response, and Akt Signaling In Vitro

Abstract: Due to their distinctive physicochemical properties, platinum nanoparticles (PtNPs) have emerged as a material of interest for a number of biomedical therapeutics. However, in some instances NP exposure has been correlated to health and safety concerns, including cytotoxicity, activation of cellular stress, and modification to normal cell functionality. As PtNPs have induced differential cellular responses in vitro, the goal of this study was to further characterize the behavior and toxicological potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The entire reaction was completed within 2 h due to the presence of pure phenolic compounds in the solution. The single sharp peak at 300 nm was attributed to the excitations of surface plasmon vibrations, indicating the synthesis of PtNPs (Figure 1A), which is in agreement with the results of previous reports [41,42]. Several studies have reported that metal nanoparticles can be synthesized using biomolecules as reducing and stabilizing agents.…”
Section: Resultssupporting
confidence: 90%
“…The entire reaction was completed within 2 h due to the presence of pure phenolic compounds in the solution. The single sharp peak at 300 nm was attributed to the excitations of surface plasmon vibrations, indicating the synthesis of PtNPs (Figure 1A), which is in agreement with the results of previous reports [41,42]. Several studies have reported that metal nanoparticles can be synthesized using biomolecules as reducing and stabilizing agents.…”
Section: Resultssupporting
confidence: 90%
“…Platinum NPs induce ROS generation by impairing receptor activator of nuclear factor κB ligand (RANKL) signaling [48]. For instance, incubating HepG2 cells with 68-nm PtNPs suggested that ROS are dose-dependently induced [34]. Ultra-small PtNPs also induce ROS generation in THP-1 cells [22].…”
Section: Platinum-based Nps Induce Ros Lipid Peroxidation (Lpo) Nitmentioning
confidence: 99%
“…Platinum NPs induce size-dependent toxicity in neuroblastoma, MDA-MB-231, and LNCaP cells, indicating that the diameter of these NPs plays a crucial role in cytotoxicity [33]. Graphene oxide and vanillin-functionalized graphene oxide induce pro-inflammatory cytokines in a human acute monocytic leukemia cell line [22], and PtNPs dose-dependently induce cytokines such as IL-1β, IL-8, and tumor necrosis factor alpha (TNFα) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that high doses of PtNPs (70 nm, citrate coated) induced HepG2 cytotoxicyty. Lower concentrations did not induce direct toxicity, but the combined presence of intracellular stress, active inflammatory responses with upregulated signal transduction might have influence on long-term health hazards [42].…”
Section: In Vitro Studiesmentioning
confidence: 90%